2017
DOI: 10.1108/prt-04-2016-0042
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of water-resistant adhesives from soy flour with less water-soluble components for wood bonding

Abstract: Purpose The purpose of this paper is to prepare a water-resistant adhesive (SA) from soy flour (SF) with less water-soluble components. Design/methodology/approach Defatted SF was suspended and stirred in water. Then, the pH of dispersion was adjusted to a predetermined value (i.e. 8, 9 or 10) by the addition of 2M sodium hydroxide (NaOH) solution. After stirring at a predetermined temperature (25°C, 35°C, 45°C) for different time (1 h, 2 h, 3 h), the 2M hydrochloric acid (HCl) solution was added in a dropwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Gui et al centered their research on the preparation of water-resistant soy flour adhesives through the reduction in the water-soluble constituents [120]. Previous research has shown that poor water resistance is mainly caused by feedstock water-soluble components [29].…”
Section: Removal Of Hydrophilic Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Gui et al centered their research on the preparation of water-resistant soy flour adhesives through the reduction in the water-soluble constituents [120]. Previous research has shown that poor water resistance is mainly caused by feedstock water-soluble components [29].…”
Section: Removal Of Hydrophilic Contentmentioning
confidence: 99%
“…Previous research has shown that poor water resistance is mainly caused by feedstock water-soluble components [29]. The design approach involved suspending the defatted soy flour in water followed by the adjustment of the dispersion pH at different temperatures and time points to 4.5 by adding NaOH and HCl solution, respectively [120]. Then, the sample with less water-soluble constituents was separated through a centrifugation [120].…”
Section: Removal Of Hydrophilic Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance the water resistance of adhesives, several aspects have been investigated, including increasing the cross-linking within the adhesive material, adding modified fillers, , and removing hydrophilic content or introducing hydrophobic components. , However, these methods normally involve synthetic materials and complicated treatment processes and still do not deliver long-term water resistance. Learning from nature, a promising strategy for improving the water resistance of adhesives is to mimic the wet adhesion mechanisms of mussels. These marine organisms secrete a complex protein-based adhesive, enabling firm attachment to various substrates underwater.…”
Section: Introductionmentioning
confidence: 99%
“…However, the low bonding strength, poor water and mildew resistance of the protein-based adhesives have limited their applications. Up to date, some modification methods have been effective in improving the performances of soybean protein adhesive, such as denaturing agent- [8], cross-linking agents- [9,10], and biomimetic chemistry modification [11], etc. However, all of these methods involved in using the fossil resources, and the modification process is cumbersome, which have increased the cost and processing time for the adhesive preparation.…”
Section: Introductionmentioning
confidence: 99%